2012
DOI: 10.1016/j.neurobiolaging.2011.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes in aged nonhuman primate brain gray matter synthesize excess hyaluronan

Abstract: The glycosaminoglycan hyaluronan (HA) accumulates in central nervous system lesions where it limits astrogliosis but also inhibits oligodendrocyte progenitor cell (OPC) maturation. The role of hyaluronan in normative brain aging has not been previously investigated. Here, we tested the hypothesis that HA accumulates in the aging non-human primate brain. We found that HA levels significantly increase with age in the gray matter of rhesus macaques. HA accumulation was linked to age-related increases in the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
66
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 60 publications
5
66
0
2
Order By: Relevance
“…A variety of conditions that reduce cerebral blood flow, including reduced angiogenesis, tortuous arterioles, and hypoxia-induced loss of capillaries, may each result in WM damage in the elderly (Fernando et al 2004;Brown and Thore 2011). The finding that myelin-and axon-associated free radical injury, as assessed by measurements of distinct isoprostanes, inversely correlated with FA in vascular brain injury independent of AD (Back et al 2011) support a model whereby vascular changes cause age-related WM damage through oxidative stress. Fig.…”
Section: Mechanisms Of Wm Changes During Normative Agingmentioning
confidence: 80%
See 4 more Smart Citations
“…A variety of conditions that reduce cerebral blood flow, including reduced angiogenesis, tortuous arterioles, and hypoxia-induced loss of capillaries, may each result in WM damage in the elderly (Fernando et al 2004;Brown and Thore 2011). The finding that myelin-and axon-associated free radical injury, as assessed by measurements of distinct isoprostanes, inversely correlated with FA in vascular brain injury independent of AD (Back et al 2011) support a model whereby vascular changes cause age-related WM damage through oxidative stress. Fig.…”
Section: Mechanisms Of Wm Changes During Normative Agingmentioning
confidence: 80%
“…A similar result showed that normal aged and mildly cognitively impaired (MCI) subjects differed from AD, in that the latter had a differential decrease of FA in the left anterior temporal lobe, consistent with disease progression (Damoiseaux et al 2009). Interestingly, lower FA was associated significantly with coincident AD and vascular brain injury (Back et al 2011). Given that AD and vascular brain injury are commonly co-morbid (Sonnen et al 2009), it is possible that earlier findings of lower FA in AD patients reflected vascular disturbances as opposed to a specific effect of AD pathology.…”
Section: Wm and Alzheimer's Diseasementioning
confidence: 90%
See 3 more Smart Citations